ANALYSIS OF THE HADITH ON THE PRINCIPLE OF TRANSPARENCY IN BUYING AND SALE TRANSACTIONS AND ITS APPLICATION IN SYARIAH E-COMMERCE - Kholik, Jamaludin Acmad (Nabawi: Journal of Hadith Studies, 2024)
This research underscores the critical role of transparency in sales transactions as delineated in the hadiths of Prophet Muhammad SAW and examines its relevance in Shariah-compliant e-commerce. In the context of rapid technological advances and the surge in online transactions, it is imperative to uphold fairness and transparency. The study aims to scrutinize hadiths pertaining to trade transparency and their application in Shariah-compliant e-commerce. Utilizing a qualitative library research approach, this study includes an examination of hadith books, relevant literature, journals, and articles. The key findings reveal a strong emphasis on honesty and transparency in hadiths to prevent fraud and maintain trust between sellers and buyers. Within Shariah-compliant e-commerce, these principles manifest in providing precise product descriptions, adhering to halal certification standards, implementing transparent return policies, and maintaining an honest review system. Ultimately, adhering to transparency principles as guided by hadiths fosters consumer trust and satisfaction, thereby establishing a fair and ethical business environment. [Penelitian ini menekankan pentingnya prinsip keterbukaan dalam transaksi jual beli sesuai dengan ajaran hadis Nabi Muhammad SAW, dan mengeksplorasi penerapannya dalam e-commerce yang sesuai dengan syariah. Dengan kemajuan teknologi yang pesat dan peningkatan transaksi online, sangat penting untuk memastikan bahwa prinsip keadilan dan transparansi tetap terjaga. Tujuan dari penelitian ini adalah menganalisis hadis yang terkait dengan keterbukaan dalam perdagangan dan bagaimana prinsip tersebut dapat diterapkan dalam e-commerce syariah. Metode yang digunakan adalah penelitian kepustakaan dengan pendekatan kualitatif, yang mencakup kajian terhadap kitab-kitab hadis, buku, jurnal, dan artikel terkait. Temuan utama menunjukkan bahwa hadis sangat menekankan pentingnya kejujuran dan keterbukaan untuk mencegah penipuan dan mempertahankan kepercayaan antara penjual dan pembeli. Dalam konteks e-commerce syariah, penerapan prinsip-prinsip ini mencakup penyediaan deskripsi produk yang jelas dan akurat, sertifikasi halal, kebijakan pengembalian yang transparan, serta sistem penilaian dan ulasan konsumen yang jujur. Kesimpulannya, dengan menerapkan prinsip keterbukaan sesuai dengan pedoman hadis, e-commerce syariah dapat membangun kepercayaan dan kepuasan konsumen, serta menciptakan lingkungan bisnis yang adil dan etis.]